A miniature and low-cost glucose measurement system - Adams, S.D.; Buber, E.; Bicak, T.C.; Yagci, Y.; Toppare, L.; Kaynak, A.; Kouzani, A.Z. (Elsevier BV, 2018)
Abstract One of the bottlenecks in widespread adoption of biosensors is the large and sophisticated bioanalytical system that is required to perform signal transduction and analysis. A miniaturized bioanalytical system facilitates biosensing techniques that are portable, easy to handle and inexpensive for fast and reliable measurements of biochemical species. Thus, downscaling the bioanalytical system has become a highly active research area, significantly assisted by recent advances in the microelectronics technology. In this work, a miniaturized system is designed and implemented for amperometric detection, and subsequently tested with a glucose biosensor based on the one-step approach utilizing water soluble poly(o-aminophenol). Several experiments are conducted to assess the viability of this system including calibration, interference and application tests. The results are compared with the previously published work performed using the same biosensor tested with a commercial potentiostat in order to verify the applicability of the designed system.